2017
DOI: 10.2967/jnumed.117.191718
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of the Programmed Death Ligand 1 by 18F PET

Abstract: Programmed death ligand 1 (PD-L1) is an immune regulatory ligand that binds to the T-cell immune check point programmed death 1. Tumor expression of PD-L1 is correlated with immune suppression and poor prognosis. It is also correlated with therapeutic efficacy of programmed death 1 and PD-L1 inhibitors. In vivo imaging may enable real-time follow-up of changing PD-L1 expression and heterogeneity evaluation of PD-L1 expression across tumors in the same subject. We have radiolabeled the PD-L1-binding Affibody mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…Uptake in non-tumor tissues was low, with the highest signals in kidney and bladder, reflecting excretion, but also in liver, which showed non-negligible uptake of the radiotracer. Ex vivo autoradiography of mixed PD-L1 pos and PD-L1 neg tumors showed heterogeneous uptake, with areas of highest radiotracer uptake corresponding to PD-L1 positivity on IHC 70 .…”
Section: Introductionmentioning
confidence: 97%
“…Uptake in non-tumor tissues was low, with the highest signals in kidney and bladder, reflecting excretion, but also in liver, which showed non-negligible uptake of the radiotracer. Ex vivo autoradiography of mixed PD-L1 pos and PD-L1 neg tumors showed heterogeneous uptake, with areas of highest radiotracer uptake corresponding to PD-L1 positivity on IHC 70 .…”
Section: Introductionmentioning
confidence: 97%
“…Affinity maturation permits a further increase of the affinity from a few nM to a few pM. High-affinity affibody binders have been selected for potential cancer-associated molecular targets such as human epidermal growth factor receptor type 2 (HER2) [22], epidermal growth factor receptor (EGFR or HER1) [23], human epidermal growth factor receptor type 3 (HER3) [24], insulinlike growth factor-1 receptor (IGF-1R) [25], platelet-derived growth factor receptor β (PDGFRβ) [26], vascular endothelial growth factor receptor 2 (VEGFR2) [27], programmed death-ligand 1 (PD-L1) [28], and carbonic anhydrase IX (CAIX) [29]. Several features of affibody molecules make them potentially attractive as targeting vectors for imaging probes:…”
Section: Engineered Scaffold Protein-based Imaging Probes: Affibody Mmentioning
confidence: 99%
“…[ 18 F]-AlF-NOTA-ZHER2:2395 demonstrated excellent tumor targeting 4 h pi (tumor-to-blood ratio of 145 ± 24), but the bone uptake was twice as high as that of its 111 In-labeled counterpart, which indicates a somewhat lower chelate stability. This approach has been applied to label the HER2-binding affibody molecules NOTA-CGGGRDN-ZHER2:234 [86], and NOTA-ZHER2:2891-C [58], PD-L1-binding NOTA-ZPD-L1_1 [28], and EGFR-binding NOTA-ZEGFR:1907 [87] and NOTA-ZEGFR:03115 [88], providing radiochemical yields in the range of 10-15% after a 40-min procedure. Another efficient approach for improving the radiofluorination yield is based on the formation of [ 18 F]aluminium monofluoride ([ 18 F]-AlF), with subsequent complexation by derivatives of the NOTA chelator [85].…”
Section: Fluorine-18mentioning
confidence: 99%
“…Despite the tremendous potential of antibody‐based tracers, they have slow blood clearance that leads to long waiting time (eg, several days) between imaging scan and tracer injection, which prevents the clinical transformation of the molecular imaging. In this setting, a number of protein‐ or peptide‐based radiotracers have been fabricated to compensate the pitfalls of the antibody‐based probes . For example, Trotte et al developed a 18 F‐labeled affibody ligand that can effectively detect PD‐L1 expression in xenograft tumors by PET imaging, with preferable specificity, fast blood clearance, and low normal tissue uptake except nephridia .…”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…In this setting, a number of protein‐ or peptide‐based radiotracers have been fabricated to compensate the pitfalls of the antibody‐based probes . For example, Trotte et al developed a 18 F‐labeled affibody ligand that can effectively detect PD‐L1 expression in xenograft tumors by PET imaging, with preferable specificity, fast blood clearance, and low normal tissue uptake except nephridia . Larimer et al demonstrated that granzyme B PET imaging might serve as an effective biomarker for predicting responses to immunotherapy in human tumor xenograft models …”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%